Iatrogenic Small Intestine Perforation During Suprapubic Catheter Change - Naveen Kumar; Kashif Rizwi; Saket Singh; Shashikant Kumar (Société Internationale d’Urologie Journal)
A gentleman in his 70s presented to the emergency department with diffuse abdominal pain, abdominal distention, and anuria of 3-days duration [...]